MitraClipVR as bridging strategy for heart transplantation in chagas cardiomyopathy: a case report (2020)
Background Patients with end-stage heart failure, suffering from severe pulmonary hypertension (PH) and elevated pulmonary vascular resistance, are not eligible for heart transplant due to high mortality risk and primary graft dysfunction. Severe PH may be favoured by functional severe mitral regurgitation, which is present in many cardiopathies like end-stage Chagasic cardiomyopathy. Case summary We present a case of a young man with end-stage heart failure secondary to Chagas cardiomyopathy with severe functional mitral regurgitation (FMR) and severe PH. The patient received percutaneous correction with MitraClipVR system reducing PH and making him a suitable candidate for heart transplant. Discussion In patients with advanced heart failure, FMR, and severe PH, optimal treatment according to current guide lines is recommended. MitraClipVR therapy appears to be safe and effective for control of severe PH as a bridge measure for cardiac transplantation.